Is sustainability a moving target? A methodology for measuring CSR dynamics. (26th June 2019) - Zeisel, Stefan
Abstract: Sustainability is a subject that is constantly evolving. This article develops a quantitative methodology to measure the dynamics of sustainability topics based on corporate social responsibility (CSR) reports. This methodology is then used to analyse the dynamics of sustainability over 5 years (2011 vs. 2016) of the largest publicly traded German companies. Studying the CSR reports over time reveals that CSR is often very dynamic at the company level but less so within a sector or overall. Environmental dynamics therefore challenge companies to focus on the right CSR topics. Some companies fare better than others in this dynamic environment. Furthermore, first insights for managing sustainability dynamics are discussed.